PEMANFAATAN E-COMMERCE SEBAGAI BENTUK TRANSFORMASI DIGITAL PENJUALAN BAGI PELAKU UMKM - Triesia, Diah; Putri, Intan; Dwipa, Ruswa; Rizki, Rani Ria (Jurnal Teknik Informasi dan Komputer (Tekinkom), 2025)
This research explores the utilization of e-commerce as a form of digital transformation in sales among Micro, Small, and Medium Enterprises (MSMEs) in Palembang City. The rapid development of digital technology has significantly influenced the business sector, particularly MSMEs that are required to adapt in order to stay competitive. The study aims to analyze how MSME actors in Palembang adopt e-commerce platforms to improve business performance, expand market reach, and enhance customer engagement. Using a qualitative descriptive approach, data were collected through in-depth interviews with selected MSME owners and analyzed using thematic analysis. The findings reveal that although awareness and adoption of e-commerce among MSMEs are increasing, many still face challenges related to digital skills, infrastructure, and consistent online marketing strategies. The results indicate that e-commerce adoption has contributed to an average sales increase of 25–40%, reduced operational costs, and enabled penetration into new market segments outside the local area. The discussion highlights that the successful integration of e-commerce requires not only technical readiness but also continuous digital literacy, promotional consistency, and supportive government policies. In conclusion, digital transformation through e-commerce is not only a technological shift but also a strategic necessity for MSMEs in Palembang to sustain competitiveness, improve operational efficiency, and achieve long-term business growth in the digital economy era.